Islamic NGO as another actor of Civil Society: the Case of Pertubuhan IKRAM Malaysia (IKRAM) - Maszlee Malik; Safwan Safarudin; Hamidah Mat (Universiti Sains Islam Malaysia, 2024)
The role of Non-Governmental Organizations (NGOs) in the development of society has been the focus of academic study since the nineteenth century based on the positive contributions of the private sector in spearheading the general and specific roles in the society. The post-Cold War world has witnessed the emerging of NGOs as an alternative to the states due to the liberalization of global economy worldwide. It was since then the academic interest on this phenomenon has risen in particular in the late 1980s when NGOs has managed to replace governments' role in reaching out to the people, or in other cases becoming the voice of the people before the governments. This study aims to explore the dynamic roles of NGOs in leading the change and reforms in the modern society and how Islamic organization could fit into the framework by critically looking into the experience of Pertubuhan IKRAM Malaysia (IKRAM), a Malaysian-based Islamic organization as a case study. While the results reveal some positive impacts on the society, they also exhibit some challenges and conflicts when the evolution reaches certain stages of time and space, illustrating the dynamic nature of IKRAM as both an Islamic organization and NGO with respect to strategies, resources and strategic actions.